The Immunological Properties of Recombinant Multi-Cystatin-Like Domain Protein From Trichinella Britovi Produced in Yeast - Stachyra, Anna; Zawistowska-Deniziak, Anna; Basałaj, Katarzyna; Grzelak, Sylwia; Gondek, Michał; Bień-Kalinowska, Justyna (Frontiers in Immunology, 2019)
Trichinellosis is a globally-distributed zoonotic parasitic disease caused by nematode worms of the genus Trichinella. One of the most common species of Trichinella known to affect human health is T. britovi; however, it is relatively poorly investigated. A thorough knowledge of the proteins expressed by Trichinella is important when developing immunological detection methods and vaccines and studying its interactions with the host. The present study uses the P. pastoris expression system to produce a soluble TbCLP antigen which induces strong antibody responses in the host during natural infection. Our results demonstrate the feasibility of TbCLP antigen production in yeasts, which are able to carry out posttranslational modifications such as glycosylation and disulfide bond formation; they also indicate that the glycosylated TbCLP antigen had immunogenic effects in the tested mice and induced a mixed Th1/Th2 response, and was associated with a reduced larval burden after challenge with T. britovi. Subsequent in vitro stimulation of mice splenocytes revealed that TbCLP most likely possesses immunomodulatory properties and may play a significant role in the early phase of infection, affecting host immunological responses.